Sistem Pendukung Keputusan Pemilihan Sales Terbaik Menggunakan Metode Topsis - Rizani, Moh Asra; Pibriana, Desi; Amelia Fransen, Lisa (Universitas Multi Data Palembang, 2024)
PT Berkah Trijaya Indonesia is a company engaged in telecommunications official distribution xl center in Palembang. PT Berkah Trijaya Indonesia has several obstacles, namely determining the best sales currently using only criteria and not adding sub-criteria in the calculation. So that with the best sales assessment system at this time is not fair. The TOPSIS method was chosen based on its simplicity and efficient computation, so that in the company's calculations in determining the best sales without weight, while TOPSIS gives weight to the assessment. The ranking results of the two calculations are different, showing computational fairness is better using TOPSIS. Therefore this research uses the TOPSIS method. The system was built to build a best sales selection decision support system that can manage sales data and assessment parameters properly. The sales system built can manage sales data, criteria data, sub criteria data, store assessment data, calculate sales scores and provide rankings for each sales using the TOPSIS method. The system was built using the RUP methodology. The result of this research is a decision support system that ranks the best sales based on the assessment results calculated using the TOPSIS method.